O acaso, o poeta e a re-visão da ciência no límen do milênio - Toneto, Diana Junkes Martha [UNESP] (My University, 2010)
The second part of the poem A Máquina do Mundo Repensada, from Haroldo de Campos (2000), is very inventive as it brings up, to the center of this text, composed in terza rima, the science as the poetic message protagonist. If at the first part of the poem there is a return to the tradition texts, at the second, although these dialogues remain, the impulse to the newness is guaranteed by the ingress of the scientific theme in the poem, which conducts the poetic person to new ways, to unknown places and makes more emphatic the possibility of establishment of the literary text as the scene of modern physics discoveries, but, at the same time the poetic word inquires these discoveries. At the second part of the haroldian poem, which analysis is presented here, the literary frontiers' challenge tangencies the science frontiers. All of this makes Haroldo a poet of the absolutely new.
The chance, the poet and the science re-view by the limen of the millennium
Keywords: A Máquina do Mundo Repensada; Haroldo de Campos; Modernity; Poetry; Quantic physics; Science